Urban tourism and Covid-19 in Poland - Karolina Józefowicz (REGION, 2021)
World Tourism Organisation estimates an 80% drop in tourist arrivals by the end of 2020. The Polish tourism industry is also dramatically affected by the ongoing pandemic, with a 30% drop in the number of tourists in July 2020 compared to July 2019. The global lockdown has limited the functioning of the tourism sector, therefore domestic tourism, including urban tourism, may rise in importance. Domestic urban tourism can become a useful response to the growing resilience of the tourism industry, for example in the context of reducing dependence between the tourism industry and mobility which favours the spread of coronavirus. The potential of urban tourism in Poland is clearly visible (in 2019, it was three times higher than rural tourism in terms of overnight stays provided). However, the COVID-19 pandemic is not conducive to urban tourism in Poland, for instance, because infections are much more frequent in cities than in rural areas. The aim of the research, in addition to checking destinations of Poles in the context of urban tourism in the era of the pandemic, was to learn about the behaviour of tourists during their holiday trips. To achieve the aim of the paper, the study was conducted from 16 to 31 August 2020, using CAWI survey method, among people who visited Polish cities starting from May 2020 through the end of August 2020 (following the partial lifting of restrictions). The research indicated, despite the threat, the popularity of the largest tourist destinations in Poland. It also indicated that the behaviour and decisions of tourists were not different from those before the pandemic.
Keywords: 330